Zur Problematik des Zielsystems von Mutual Funds - Manfred Adami (Kredit und Kapital, 1970)
On the Problems of the Objective System of Mutual Funds In recent times, mutual funds have attained great importance as instruments of capital investment. Their varying objective systems merit attention above all because in investing funds provided by savers the latter's target conceptions must be taken into account. 'The investor's targets and behaviour are therefore important pointers for the formation and formulation of the external objective system of the mutual funds. That system of objectives serves as an orientation aid for investors when selecting a fund. The elements of that objective system are the desire for securing the capital value, income and capital growth. They are contained to varying degrees in the objective system of all funds. In addition, there is what is described here as an "internal" objective system. This term is used for the objectives of the persons and organizations directly participating in the performance of a fund. These objectives are for the most part of a different nature than the external objectives. The main issue is the achievement of income for the participants and, since as a rule that income grows proportionally with the assets of a fund (management charges, agent's commission, sales charges accruing on expansion of the fund), those taking part in the management are usually primarily interested in the growth of the fund. The necessity of making allowances for the investor's objectives to a great extent makes special measures synthesizing diverging objective conceptions essential. Almost always, however, they are adapted only to the external objective system. Consequently conflicts of interest arise between the management's desire for income and the opposing interest of investors in leaving as much of the returns as possible in the fund. In extreme cases such conflicts of interests have led to substantial impairment of investors' interests.
Keywords: 330